The analysis of socio culture and economic influence towards Malay community of the architecture of Masjid Jamek - Ismail, Sumarni; Utaberta, Nangkula; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah (American-Eurasian Network for Scientific Information, 2015)
The objective of this paper in to convey some of the analytical studies about the impact and influence of the architecture of Masjid Jamek towards to important elements; socio culture and economic activities of Malay community at Malaysia. With the advancement and rapid progressive at Kuala Lumpur nowadays and towards its vision to be the world-class city it is very important for use to ponder and reevaluate the contribution of the ‘historical’ building before we can step forward and ‘open a new leaf’ or our future mission. Therefore, hopefully, this paper can be a starting point and good for the Malaysian citizen to bear in their mind and then realize that we most appreciate the past before we can generate our effort by heart and soul to archive the future ambition.